A COMPLETE DESIGN METHODOLOGY FOR LEAN IN-PLANT LOGISTICS TO ASSEMBLY LINE USING AD PRINCIPLES - (:unkn) unknown (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2019)
Implementation of lean philosophy has gained importance since it has achieved an outstanding success especially in production systems. Principles of lean production are different from traditional systems, where parts feeding and material handling activities are performed differently especially in small lot production. Integration and coordination of these activities increase the efficiency of lean systems. In this paper, a complete design for in-plant logistics activities is performed via Axiomatic Design (AD) principles. A four-step design methodology from parts line side presentation through in-plant vehicle routing is proposed. Proposed design methodology in AD aims to decrease the information requirement of assembly line in-plant logistics design. From practitioners' perspective, most important design steps are arranged and Functional Requirements (FRs) are emphasized. Based on the FRs, comprehensive list of Design Parameters (DPs) are defined and interactions are highlighted. Both FRs and DPs are supported with literature and practical applications. The relations between lean principles, DPs and lean tools are evaluated and the justification of the proposed design is shown. To the best of authors' knowledge, this study is the first attempt in an integrated design of in-plant logistics activities. The findings of the study also point out voids in the literature and shed light on future studies.
Keywords: lean in-plant logistics; axiomatic design; continuous improvement; integration of logistics activities; MATERIAL HANDLING-SYSTEM; TRAVEL DISTANCE ESTIMATION; ORDER-PICKING; STORAGE ASSIGNMENT; AXIOMATIC DESIGN; WAREHOUSE; MODEL; SELECTION; TIME; EQUIPMENT